Study on Mechanisms of NOx and SOx Formation in a Marine Diesel Engine Based on Quantum Chemistry - Zhou, Song; Zhu, Yuanqing; He, Guojing (Asian Journal of Chemistry, 2012)
This paper presents the study on mechanisms of NOx and SOx formation in a marine diesel engine and models about NOx and SOx formation were set up based on theory of quantum chemistry. The new NOx model covers thermal NO, prompt NO, fuel NO and NO via N2O, etc. SOx formation model discovers the detailed composition changes of sulphur-contained materials during combustion process. The correction and availability of the models were proved by engine emission tests. In the last, simulations of NOx and SOx formation in a marine diesel engine were carried out and by that the laws of engine parameters on engine emissions were obtained. The models suggested in present work can do help to reduce engine emissions.